Persepsi Orang Tua Muslim tentang Hak Anak dalam Praktik Khitan: Implikasi Pedagogis bagi Pendidikan Islam Berbasis Keluarga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Circumcision practices within Muslim families are not only understood as a religious ritual, but also as part of parents' responsibility to fulfill children's rights and instill Islamic educational values from an early age. However, parents' perceptions of children's rights in the practice of circumcision are often influenced by religious, cultural, health, and service access factors, which have direct implications for family-based Islamic education patterns. This study aims to analyze Muslim parents' perceptions of children's rights in the practice of circumcision and its pedagogical implications for Islamic education within the family. This research uses the literature study method by systematically reviewing scientific literature such as journals, books, and policy documents relevant to the themes of family Islamic education, children's rights, and circumcision practices. Data were analyzed using a descriptive-analytical approach and conceptual synthesis to identify patterns in the findings and relationships between concepts. The study results indicate that parental perceptions are multidimensional, encompassing religious, cultural, medical, ethical, and structural dimensions. It was also found that there is a gap between the ideal values of Islamic family education, which emphasize protecting the dignity and safety of children, and ritual practices that still tend to be traditional and mechanical. The pedagogical implications of this research underscore the importance of reorienting family-based Islamic education toward a more holistic, reflective, and child rights-sensitive approach. Integrating the values of children's rights, health literacy, and supportive healthcare policies is key to aligning circumcision practices with the principles of Islamic education and child protection.